GAMBARAN KONSUMSI MAKANAN DAN STATUS ANEMIA IBU HAMIL SAMPEL PENELITIAN SUMMIT (THE SUPPLEMENTATION WITH MULTIPLE MICRONUTRIENTS INTERVENTION TRIAL) DI LOMBOK - Sri Prihatini; Abas Basuni Jahari; Susy Sebayang; Iswidahni Iswidahni (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2009)
FOOD CONSUMPTION AND ANAEMIA STATUS ON PREGNANT WOMEN SAMPLE STUDY SUMMIT  (THE SUPPLEMENTATION WITH MULTIPLE MICRONUTRIENTS INTERVENTION TRIAL) IN LOMBOK.Background: Information on consumption pattern is key to the analysis of trial results suchas the SUMMIT (supplementation multiple micronutrients intervention trial) as consumption modifies the outcome of intervention. It is therefore important to prove that nutrient consumption is comparable between the two groups (iron folate vs. multiple micronutrient) in the SUMMIT trial.Objectives: to analyse food consumption and anemia status of pregnant women at enrolment to both groups in the SUMMIT trial.Methods: This paper analysed consumption data of 16,111 pregnant women in the SUMMIT cohort that was collected prior to supplementation. As many as 7722 of the samples belong to the iron folate (IFO) group and 8389 belong to women who received multiple micronutrients. Data was collected by trained field data collector using the 1x24 hr recall method. Around the same time of the recall, data of haemoglobin level were taken with Hemocue. Nutrient consumption status was assessed using the 2004 Indonesian recommended daily allowance (RDA). Calculation of the nutrient composition was done with Nutrisoft software. The difference and relation between consumption and anemia status between the two groups were determined using Chi-square and T-test.Results: The average consumption of macronutrient and micronutrient in the samples were only around 50% of RDA. Around 80% of the samples were energy deficient and around 75% were protein deficient (<70% RDA). Hemoglobin level of those enrolled in the first trimester was 11.7 (g/dl), which was higher compared to those enrolled in the second (10.9 g/dl) and third trimester (10.5g/dl). The proportion of anemic women enrolled in the first trimester was lower compared to those enrolled in the second and third trimester.Conclusions: Pregnant women in Lombok consumed macro and micronutrient far less than recommended. Both the IFO and MMN group of the cohort were comparable in terms of nutrient consumption.Recommendations: Because nutrient consumption of pregnant women was far lower than the RDA, both macro and micronutrient consumption of pregnant women need to be addressed in order to improve maternal nutritional status. The programmatic implication is that maternal micronutrient supplementation needs to be combined with macronutrient intervention in order to obtain its optimal outcome.Keywords: pregnant women, energy and protein consumption, anemia.